Injectable Self-Healing Adhesive pH-Responsive Hydrogels Accelerate Gastric Hemostasis and Wound Healing - He, Jiahui; Zhang, Zixi; Yang, Yutong; Ren, Fenggang; Li, Jipeng; Zhu, Shaojun; Ma, Feng; Wu, Rongqian; Lv, Yi; He, Gang; Guo, Baolin; Chu, Dake (Nano-Micro Letters, 2021)
Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are well-established therapeutics for gastrointestinal neoplasias, but complications after EMR/ESD, including bleeding and perforation, result in additional treatment morbidity and even threaten the lives of patients. Thus, designing biomaterials to treat gastric bleeding and wound healing after endoscopic treatment is highly desired and remains a challenge. Herein, a series of injectable pH-responsive self-healing adhesive hydrogels based on acryloyl-6-aminocaproic acid (AA) and AA-g-N-hydroxysuccinimide (AA-NHS) were developed, and their great potential as endoscopic sprayable bioadhesive materials to efficiently stop hemorrhage and promote the wound healing process was further demonstrated in a swine gastric hemorrhage/wound model. The hydrogels showed a suitable gelation time, an autonomous and efficient self-healing capacity, hemostatic properties, and good biocompatibility. With the introduction of AA-NHS as a micro-cross-linker, the hydrogels exhibited enhanced adhesive strength. A swine gastric hemorrhage in vivo model demonstrated that the hydrogels showed good hemostatic performance by stopping acute arterial bleeding and preventing delayed bleeding. A gastric wound model indicated that the hydrogels showed excellent treatment effects with significantly enhanced wound healing with type I collagen deposition, α-SMA expression, and blood vessel formation. These injectable self-healing adhesive hydrogels exhibited great potential to treat gastric wounds after endoscopic treatment. Highlights: 1 A series of novel injectable pH-responsive self-healing hydrogels with enhanced adhesive strength were prepared. 2 The hydrogels showed good gastric hemostasis property in a swine gastric hemorrhage model. 3 The hydrogels greatly enhanced gastric wound healing in a swine gastric wound model.